Knowledge management system architecture in agricultural industries environment - Abdullah, Rusli; Jaafar, Azmi; Ibrahim, Hamidah; Selamat, Mohd Hasan; Napis, Suhaimi; Atan, Rodziah (IEEE, 2008)
Knowledge Management (KM) has emerged as the hottest topic in the entire global world of business. Its contributions toward the successful of the organizations are currently been proved and saluted. The power of KM as a system is no longer possesses any limitations. In fact, many KM system practitioners have claimed it as the most desired and demanded energizer to the organizations today, as the role it plays is absolutely important. The role of KM system could be determined by looking on technicalities issues, challenges and opportunities of how to make sure that the right knowledge could be disseminated to the right people at the right time for any purposes. Besides that, KM also could be looked on how the processes involved in gathering and storing the knowledge in the proper placing and formating it as well to be able to access or use when it is needed. While, the agriculture-based industries environment which deal with business of plantation, forestries, and animals, including soil cultivation, crop and livestock management as well as many other activities which have a lot of potential to promote knowledge sharing among its community of practice (CoP) in term of best practice and lesson learnt. This paper analyzes the concept and the system architecture of KM in the agriculture-based industries and discusses various aspects in terms of its technicalities of KM system (KMS) as well as issues, challenges and opportunities involved in this field that will help CoP to increase their productivity and quality as well as to gain return on investment (ROI).